Dinamika Regulasi Emosi Ibu Dalam Penanganan Meltdown dan Tantrum Pada Anak Dengan Autism Spectrum Disorder (ASD) - Suryaganda, Sylvia Dewi; Herabadi, Astrid Gisela (ANIMA Indonesian Psychological Journal, 2024)
This study aims to understand the dynamics of mothers’ emotion regulation in handling meltdowns or tantrums in children with autism spectrum disorder (ASD). The dynamic includes the emotional regulation process, the methods for handling children’s meltdowns and tantrums, as well as the contributing factors. This study is a qualitative research, which data was collected through interviews with three study participants. Study results show that study participants utilize the five models of emotion regulation developed by Gross (2007), namely: (1) situation selection; (2) situation modification; (3) attention deployment; (4) cognitive change; and (5) response modulation. In this study, one of the findings was related to how the mothers’ condition can affect the way mothers regulate emotions. When the study participants are in a conducive condition, cognitive change tend to be prioritized before response modulation, and vice versa. Factors that affect mothers’ emotional regulation in handling meltdowns or tantrums are: (1) personal health; (2) personality; (3) mood; (4) busyness; (5) aspirations; and (6) interactions with other family members at home.